ANALYSIS STUDENT CONSELOR KNOWLEDGES ABOUT TOOTH IMPACTION IN THE HIGH SCHOOL TEGAL - Yayun Siti Rochmah; Jaka Kusnanta; Prima Agusmawanti; Rama Putranto (Jurnal Medali, 2022)
Background: The problem of impacted teeth is often asked by high school students. A student conselor must be provided with knowledge related to impacted teeth and their impact. The purpose of this study was to determine the level of knowledge of student conselors about impacted teeth.Method: Questionnaires were distributed to 40 student conselors, before and after counseling, then the differences were analyzed using SPSS.Result: Based on statistical calculations, the p value of 0.000 (p <0.05) means that there was a significant difference between the knowledge of student conselors before and after counseling. Conclusion: there was a difference in tooth impaction knowledges between before counseling and after counseling